دور أكاديميات الدعم في التقويم التربوي للتلاميذ من وجهة نظر الأمهات - حشيفة,ناجية; جار الله,سميحة (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى الكشف عن دور أكاديميات الدعم في التقييم التربوي من وجهة نظر أولياء الأمور، حيث ارتكزت على سؤال رئيسي وهو: هل تساهم أكاديميات الدعم في التقييم التربوي للطلبة، وتضمن أسئلة فرعية نذكر منها: - هل تساهم أكاديميات الدعم في تقييم الطلبة؟ - هل تساهم أكاديميات الدعم في تقييم برامج التوجيه والعلاج لمشاكل التحصيل الدراسي للطلبة؟ - هل تساهم أكاديميات الدعم في متابعة الطلبة؟ يمثل مجتمع الدراسة جميع أكاديميات الدعم بولاية الوادي، وقد تم اختيار عينة عشوائية وهي دائرة الرمل، وأفراد العينة هم أمهات طلاب السنة الرابعة متوسط الملتحقينبأكاديمياتالدعم،وقدتماعتمادالمنهجالوصفيوالإحصائي،وتماستخدامالاستبانةوالمقابلةكأدواتلجمعالبيانات،وخلصتالدراسةإلى: - لا تساهم أكاديميات الدعم في تقييم الطلبة. - تساهم الأكاديميات المساندة في تقديم برامج إرشادية وعلاجية لمشكلات التحصيل الدراسي لدى الطلبة بدرجة متوسطة. - لا تساهم الأكاديميات المساندة في متابعة الطلبة. The study aimed to reveal the role of support academies in educationalevaluation from the parents' point of view, as it was based on a mainquestion: Do support academies contribute to the educationalevaluation of students, and included sub-questions that we mention asfollows: - Do support academies contribute to the evaluation of students? - Do support academies contribute to the evaluation of guidance andtreatment programs for students' academic achievement problems? - Do support academies contribute to following up on students? The study community represents all support academies in the state of ElOued. A random sample was selected, which is the Ramal district. Thesample members are mothers of fourth-year middle school studentswho attend support academies. The descriptive and statistical approachwas adopted, and the questionnaire and interview were used as datacollection tools. The study concluded that: - Support academies do not contribute to evaluating students. - Support academies contribute to providing guidance and treatmentprograms for students' academic achievement problems to an averagedegree. - Support academies do not contribute to following up on students
Keywords: الأكاديميات المساندة (الدروس الخصوصية); التقويم التربوي; Support academies (private lessons); educational evaluation